Gender studies in Communication Degrees - García-Ramos, Francisco-José; Zurian, Francisco-A; Núñez-Gómez, Patricia (Comunicar, 2020)
This paper is the result of a research carried out under the umbrella of the "UNESCO UniTWIN Network on Media, Gender, and ICTs" Project, and it tries to determine the presence of subjects with a specific focus on gender in the current Communication Degrees offered at Spanish universities. The inclusion of subjects about gender equality in relation to media follows the suggestions of the IV EWorld Conference on WAmen in Beijing (1995). The main objective of this research will be to investigate the presence of these subjects in Communication Degrees, identifying the elements that define them at a thematic, methodological and relevant levels within the curriculum. A mixed methodological design is proposed based on ex-post-facto research, with a descriptive orientation and the search for improvement, a qualitative analysis of study plans using ATLAS.ti and a panel of experts. The results reveal a scarce presence of this type of subjects, with a higher percentage in public universities than in private ones, and also a minimal relevance as compulsory subjects. This research study reveals the current formal training in gender studies of future generations of media professionals and serves as an endorsement for forthcoming changes of curricula in the European Higher Education Area context.